Collaborative Governance for Development and Empowerment of Street Children and Beggers in The City of Palembang - Syahri Syahri; Sari Mustika Widyastuti (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The number of street children and beggars on the streets of Palembang City has increased both in number and in the area of operation. Therefore, the Palembang City Government continues to strive to provide guidance and empowerment. The purpose of this research is to analyze the collaborative governance of fostering and empowering with a qualitative descriptive method. Government and non-government stakeholders are the primary research data sources. The results of the study found that the different understandings and perspectives of each stakeholder are different in line with the main tasks and functions of the organization. This difference has an impact on the tendency to understand sectorally (sectoral ego). The Mayor's legality regarding institutional design does not guarantee effective collaboration. To build stakeholder commitment and concern, strong and trusted leadership is needed